Does Prospect Theory Explain IPO Market Behavior? - LJUNGQVIST, ALEXANDER; WILHELM, WILLIAM J. (Journal of Finance, 2005)
ABSTRACT We derive a behavioral measure of the IPO decision‐maker's satisfaction with the underwriter's performance based on Loughran and Ritter (2002) and assess its ability to explain the decision‐maker's choice among underwriters in subsequent securities offerings. Controlling for other known factors, IPO firms are less likely to switch underwriters when our behavioral measure indicates they were satisfied with the IPO underwriter's performance. Underwriters also extract higher fees for subsequent transactions involving satisfied decision‐makers. Although our tests suggest that the behavioral model has explanatory power, they do not speak directly to whether deviations from expected utility maximization determine patterns in IPO initial returns.